Kajian Temperatur Rata-rata Tertimbang (WMAPT) pada Desain Perkerasan Lentur Studi Kasus Ruas Cikampek-Pamanukan Sta 20+100 - Aloysius Tjan; Raden Hisyam Syauqi Al-Ghifari (Institut Teknologi Bandung, 2020)
AbstractThickness of flexible pavement design is affected by location temperature - this is evident in the empirical mechanistic design method when determining the dynamic modulus of asphalt mixtures. MDP recommends the representative temperature or WMAPT of 41oC while Pedoman Perencanaan Tebal Lapis Tambah recommends standard temperature of 35oC. This study analyzes the representative temperature or WMAPT with an empirical mechanistic approach. Data on axle types, axle loads and hourly temperatures are obtained for Cikampek-Pamanukan STA 20 + 100 Section. The results of the analysis showed that WMAPT is independent of pavement thickness, and subgrade resilient modulus, therefore it is valid for various pavement thickness and subgrade resilient modulus, however it depends on traffic load composition. At the study location, it is obtained an average WMAPT of 34.71oC with standard deviation of 0.5oC. Determination of WMAPT that is higher than it should be (as recommended by MDP, which is 41oC) has a potential to reduce the results of pavement life analysis. The results of this study support the standard temperature of 35oC used in Pedoman Perencanaan Tebal Lapis Tambah.AbstrakDesain tebal perkerasan lentur dipengaruhi oleh temperatur lokasi